Freeform Fabrication of Magnetophotonic Crystals with Diamond Lattices of Oxide and Metallic Glasses for Terahertz Wave Control by Micro Patterning Stereolithography and Low Temperature Sintering - Maasa Nakano (Micromachines, 2013)
Micrometer order magnetophotonic crystals with periodic arranged metallic glass and oxide glass composite materials were fabricated by stereolithographic method to reflect electromagnetic waves in terahertz frequency ranges through Bragg diffraction. In the fabrication process, the photo sensitive acrylic resin paste mixed with micrometer sized metallic glass of Fe72B14.4Si9.6Nb4 and oxide glass of B2O3·Bi2O3 particles was spread on a metal substrate, and cross sectional images of ultra violet ray were exposed. Through the layer by layer stacking, micro lattice structures with a diamond type periodic arrangement were successfully formed. The composite structures could be obtained through the dewaxing and sintering process with the lower temperature under the transition point of metallic glass. Transmission spectra of the terahertz waves through the magnetophotonic crystals were measured by using a terahertz time domain spectroscopy.